EFFECT OF MOULD CONTAMINATION OF THE AIR ON THE PERFORMANCE OF MADRAS RED LAMBS UNDER INTENSIVE SYSTEM OF MANAGEMENT - Yasotha, A; Sivakumar , T; Muralidharan , RA (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
An experiment was conducted to assess the level of mould contamination in the air of sheep pen and its influence on growth performance of lambs on slatted floor and mud floor. Weekly measurements were taken at 8 am and 2 pm for the estimation of mould count in air and climatic variables viz. air temperature, relative humidity and air velocity. The body weights of lambs were recorded fortnightly . Total mould count was significantly (P
Keywords: Mould; air borne microbes; sheep house; microclimate; floor type